Coping with COVID-19 Shocks in Western Uganda - Sharma, Ambika; Gruver, Ariel; Montalvao, Joao; O'Sullivan, Michael (World Bank, Washington, DC, 2021)
In Western Uganda, women farmers and their households were facing widespread agricultural and non-agricultural income shocks in September 2020, indicating a protracted crisis. To cope with these shocks, many households liquidated productive agricultural assets. Women who had higher decision-making power within the household before the Coronavirus disease 2019 (COVID-19) crisis, appeared to cope better with post-outbreak shocks by engaging in more income-generating activities and having better food security in the household.